KASUS GANGGUAN INTEGUMENTUM ANJING DAN KUCING DI KLINIK HEWAN JOGJA TAHUN 2014 - , EDI PITOYO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study was to determine the number of skin disorders of dog and cat at Klinik Hewan Jogja 2014. The material that was used in this thesis is based on the patient data, while the method was used directly following the activity in the Clinic and interview method was done by question and answer with the Veterinarians and Paramedics. The data were taken from our survey in Klinik Hewan Jogja during a week (April 21st â 27th, 2014). The results were handled as many as 662 patients for four months, at Klinik Hewan Jogja such as dogs with tick infestation (28 cases), fungus (120 cases), scabies (26 cases), demodecosis (22 cases) and the cats with tick infestation (77 cases), fungus (273 cases), scabies (112 cases), demodecosis (4 cases). From our studies, we concluded that dogs with tick infestation (4.23%), fungus infection (18.13%), scabies (3.92%), demodecosis (3.32%), while cats suffered tick infestation (11.63%), fungus infection (41.23%), scabies (16.92%), demodecosis (0.60%). Based on our observation above, both dog and cat pasient need to be treated not only by giving some medicine but also by improvement of the environment and grooming regularly.